Factors associated with atrial fibrillation in Japanese patients with type 2 diabetes mellitus: a cross-sectional study - Honda, Natsuki; Ochi, Akinobu; Uchimoto, Sadahiko; Kakutani, Yoshinori; Yamazaki, Yuko; Morioka, Tomoaki; Shoji, Tetsuo; Inaba, Masaaki; Emoto, Masanori (Diabetology international, 2022)
Aims Atrial fibrillation (AF) increases cardiovascular complications and mortality in patients with diabetes. Diabetes is a risk factor for AF; however, risk factors for AF among patients with type 2 diabetes (T2D) remain unknown, especially among Asian people. We clarified the prevalence of AF, regardless of type (i.e., paroxysmal, persistent, or permanent) in Japanese patients with T2D and clarified factors associated with AF. Methods This cross-sectional study was conducted at Fujiidera Municipal Hospital (Osaka, Japan). Patients with T2D ( n = 899: 518 men and 381 women with a mean age ± SD of 69.0 ± 12.1 years) were included. Their electrocardiographs were checked during routine examinations between January 2017 and January 2018. A diagnosis of AF was determined from single time-point standard 12-lead electrocardiographic findings. We analyzed clinical parameters (e.g., age, sex, diabetes duration, glycated hemoglobin, body mass index, estimated glomerular filtration rate, albuminuria or proteinuria, use of biguanide, and presence of hypertension) between patients with and without AF. Results The prevalence of AF among patients with T2D was 5.9%; it became higher as age increased and tended to be higher in men than in women. The prevalence became higher as albuminuria or proteinuria progressed and as the eGFR decreased. Multiple logistic regression analyses revealed that older age, male sex, and reduced eGFR were independently and significantly associated with the coexistence of AF. However, multiple logistic regression analysis revealed no significant relationships between AF and the presence of albuminuria or proteinuria. Conclusions Older age, male sex, and reduced eGFR were associated with AF in Japanese patients with T2D.